Tradisi Tingkeban dalam Masyarakat Perspektif Maqashid al-Syari’ah - Imaniar Mahmuda; Kurroti Akyun (Al-Qadlaya : Jurnal Hukum Keluarga Islam, 2023)
Tradition is a form of traditional ceremony carried out by the community and has become a culture that is difficult to eliminate, especially for Javanese people, as well as preserving the heritage of ancestors collectively. In the form of traditional events including the Tingkeban ritual, which is a ritual held in the seventh month of pregnancy. Tingkeban rituals that occur in each region and group can be different, this is because the intensity of external cultural influences between one region and another is different. The implementation of tingkeban rituals in an area or community group, some are based on Islamic teaching values but the custom of holding tingkeban rituals is not based on the provisions of Islamic teachings, although in Islam there is no prohibition against the tradition. Therefore, the focus of writing this article is how the process and meaning of the community about the tradition of tingkeban and how the tradition of tingkeban in society perspective maqashid al-shari'ah. The discussion of this article concludes that the community's view of the implementation of the tingkeban ritual tradition can be carried out, which is important that the community does not believe in the symbols related to the tingkeban. Tingkeban is also a manifestation of gratitude to Allah SWT so that with this tingkeban the community does one of the manifestations of gratitude and gives alms to people. The tradition of tingkeban in maqashid al-shari'ah, namely in maqashid tahsiniyyat, while what is meant by maqashid tahsiniyyat is to take a proper benefit from things that are virtues or are virtues according to custom, by avoiding circumstances that are desecrating and that are disliked by common sense. The implementation of maqashid al-shari'ah which is tahsiniyyah is intended so that humans can do something best for the improvement of the maintenance of the five principles that must be maintained, namely; religion, soul, reason, heredity, and possessions.